Discordant democrats : five steps to consensus - Maira, Arun. (New Delhi ; New York, New York : Penguin, Viking, 2007)
On the structures and systems of democracy and the role, principles, tools of consensus building.
Includes bibliographical references (p. [201]-202) and index.
Keywords: Consensus (Social sciences); Consensus (Social sciences) - India; Democracy; Democracy - India